Towards mapping the gaps in Alaska - Zimmermann, Mark; Prescott, Megan M. (The International Hydrographic Review, 2025)
In 2018, the General Bathymetric Chart of the Oceans (GEBCO) announced the Nippon Foundation-GEBCO Seabed 2030 Project to improve further the GEBCO map of the world’s oceans. The United States (U.S.) has responded with different initiatives to complete a map of its Exclusive Economic Zone (EEZ). With Alaska accounting for the greatest fraction of the U.S. EEZ, here we provide an analysis showing which portions of the National Oceanic and Atmospheric Administration’s, National Marine Fisheries Service, Alaska Fisheries Science Center (AFSC) bathymetry maps are supported by actual observations. Data support of raster cells ranged from 2.4 % to 43.4 % within six previously published AFSC bathymetry compilations, with high variability by depth and supporting hydrographic data type. This will guide new Alaska mapping efforts towards the gaps and away from remapping areas, increasing progress in fulfilling the goals of Seabed 2030 Project.